A Critical Review of Value Engineering Development in Indonesian Construction Industry - Sesmiwati, Sesmiwati; Utama, Wahyudi Putra; Roza, Fielda (-)
Instead of Value Management (VM,) term of Value Engineering (VE) in Indonesia has been known over three decades. So far, there seems to be scanty attention, if any, from academia to summarize and review practical application of VE, particularly in construction industry. This paper, therefore, attempts to encapsulate and critically review the extant of VE application in Indonesian construction industry. The review presents the development of VE, identifies the opportunities and challenges and proposes new direction for future development. Both document searching technique and literature review were undertaken to find and view the existence of the methodology. It can be said that the practical application of VE in Indonesian construction projects is running in place. Four shortfall issues contributing to this patency were identified comprising lack of regulation, promotion, knowledge and expertise. Nevertheless, there are still big opportunities to echo and develop this methodology.Â